Pemetaan Tempat Penampungan Sementara (TPS) Ilegal Menggunakan Sistem Informasi Geografis (SIG) Di Kecamatan Mandau - Michael Slamat; Jecky Asmura; Ahmad Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The total population of Mandau District in 2019 was recorded at 163,414 people with an average population growth rate of 1.46%, so the waste produced will also increase which causes an increase in the volume of waste. In addition, waste management facilities such as Temporary Shelters (TPS) provided by the Garbage Management Agency have not served all communities in Mandau District, resulting in the emergence of illegal TPS. The purpose of this study is to calculate illegal dumping volume, map the distribution of illegal dumping waste, analyze factors for the emergence of illegal dumping such as Geophysical factors, Anthropogenic factors, legal dumping availability factors, illegal TPS service factors and plan the location of illegal dumping in Mandau District. This research was conducted by tracking the study location to determine the existence of illegal dumping, and then taking the coordinates of the location using the Global Position System (GPS), then plotting coordinates using the ArcMap 10.8 software. The results found that there were 34 distribution points of illegal dumping in the study area. In the analysis of geophysical factors, based on the highest number of illegal polling stations found on local roads, there were 22 points (65%), on arterial roads as many as 11 points (32%), and collector roads as many as 1 point (3%). Based on the type of land, the highest number of illegal dumping is 26 points (76%) on the shoulder of the road and on empty land as much as 8 points (24%). Based on anthropogenic factors, at the education level the number of illegal polling stations increased along with the increase in respondents at high school level 78 people (81%). Based on the type of work, the number of illegal dumping increased along with the increase in respondents for the types of jobs of private employees and self-employed workers. Based on population density, the population density in the study location varies and has no effect on the number of illegal polling stations.Keywords: Mandau District, Mapping of Illegal Dumping, Geographic Information System (GIS).